Optimization strategies for pulsed low‐dose‐rate IMRT of recurrent lung and head and neck cancers. (8th May 2014) - Kang, Shengwei; Lang, Jinyi; Wang, Pei; Li, Jie; Lin, Muhan; Chen, Xiaoming; Guo, Ming; Chen, Fu; Chen, Lili; Ma, Chang Ming
Abstract : Pulsed low‐dose‐rate radiotherapy (PLDR) has been proven to be a valid method of reirradiation. Previous studies of recurrent cancer radiotherapy were mainly based on conventional 3D CRT and VMAT delivery techniques. There are difficulties in IMRT planning using existing commercial treatment planning systems (TPS) to meet the PLDR protocol. This work focuses on PLDR using ten‐field IMRT and a commercial TPS for two specific sites: recurrent lung cancers and head and neck cancers. Our PLDR protocol requires that the maximum dose to the PTV be less than 0.4 Gy and the mean dose to be 0.2 Gy per field. We investigated various planning strategies to meet the PLDR requirements for 20 lung and head and neck patients. The PTV volume for lung cases ranged from 101.7 to 919.4 cm 3 and the maximum dose to the PTV ranged from 0.22 to 0.39 Gy. The PTV volume for head and neck cases ranged from 66.2 to 282.1 cm 3 and the maximum dose to the PTV ranged from 0.21 to 0.39 Gy. With special beam arrangements and dosimetry parameters, it is feasible to use a commercial TPS to generate quality PLDR IMRT plans for lung and head and neck reirradiation. PACS number: 87.55.D‐